Effects of FECINOR PLUS on growth rates of calves and piglets - Tortuero F.; Riopérez J. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
Forty 0 6-week-old male Frisian calves, distributed in two groups (CONTROL and FECINOR PLUS). The test duration was divided into two periods: 6 8 weeks of age, and 8 - 14 weeks. The addition of FECINOR PLUS to the diet determined a 7.8 per cent improvement in daily weight gain during the first test period, and 8.4 per cent in the second. Feed efficiency was improved by 7.1 per cent and 6.2 per cent in the first and second periods, respectively. For weaned pigs, 50 26-day old animals, with an initial weight of 6.4 kg were used and randomly distributed in two groups, (CONTROL and FECINOR PLUS). The trial lasted three weeks. The addition of FECINOR PLUS to piglets feed (1 by 109 CFU per kg feed) resulted in a significant improvement in the daily weight gain (9.6 per cent). This additive also had positive effects on the conversion index (6.4 per cent).
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)